2015
DOI: 10.3808/jei.201500305
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Production Scheduling and Waste Management Optimization for an Oil Sands Application

Abstract: Mine planning for oil sands involves the integration of waste management into the long term production planning process. This ensures that while ore is provided for the processing plant, sufficient in-pit tailings containment areas are made available as dedicated disposal areas for backfilling. This enables the creation of a trafficable landscape at the earliest opportunity to facilitate progressive reclamation. Apart from being a regulatory requirement, this integration impacts directly on the profitability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The vials were sealed with Teflon-lined screw caps and were vortexed for 20 s, and then were placed in a reciprocal shaker at 200 rpm for 24 h to reach the sorption equilibrium. Preliminary experiments showed that 24 h were sufficient for the sorption process to reach equilibrium and the experimental loss of phenanthrene was negligible [28][29][30]. Before testing, the samples were placed for 10 min to separate the soil from the solution.…”
Section: Sorption Studiesmentioning
confidence: 99%
“…The vials were sealed with Teflon-lined screw caps and were vortexed for 20 s, and then were placed in a reciprocal shaker at 200 rpm for 24 h to reach the sorption equilibrium. Preliminary experiments showed that 24 h were sufficient for the sorption process to reach equilibrium and the experimental loss of phenanthrene was negligible [28][29][30]. Before testing, the samples were placed for 10 min to separate the soil from the solution.…”
Section: Sorption Studiesmentioning
confidence: 99%
“…Integer programming was used as a tool to assist in the decision-making process to determine the optimal locations to site a number of waste bins across a range of potential depot locations (Ben-Awuah et al, 2015). GIS software was used to determine these potential locations for waste management depots (Blanchard et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, waste disposal, reclamation planning and dyke construction planning can be well integrated with the mine planning framework. In the literature, few works have addressed such integration, but none of them has covered the mentioned domains completely (Ben-Awuah and Askari-Nasab, 2011; Ben-Awuah et al, 2012; Badiozamani and Askari-Nasab, 2012a; Badiozamani and Askari-Nasab, 2012b; Ben-Awuah, 2013; Badiozamani and Askari-Nasab, 2013a;Ben-Awuah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%